(untitled) (Journal of Forestry, 2024)
Forest fires pose a serious safety risk as they endanger human lives, damage the environment and cause material damage. Considering the significant share of forests in the total area of Croatia, fire safety is of particular interest to the Republic of Croatia. Although media and public interest in forest fires increases during the summer, probably because most fires break out in the wider coastal region, which is the most tourism-intensive part of Croatia, the causes of forest fires in Croatia are still insufficiently studied. The aim of this paper is to explore how the causes and consequences of forest fires are perceived and what solutions can be considered for their prevention. It is also analysed whether there is a difference in the perception of these issues between experts and non-experts. Experts in this paper are people who are professionally involved with forests or forest fires, and non-experts are all other respondents who visit forests as a hobby and may have come into contact with forest fires without practicing their profession. The survey was published online and was available to potential respondents from June to October 2023. During this period, the responses were collected from 119 respondents: 79 respondents are professionally involved with forests or fires and form the group of experts in this study, and 40 respondents visit forests as a hobby and form the group of non-experts. The collected responses were analysed using the Chi-square and Mann-Whitney U tests.